Desain Media Pembelajaran Berbasis Digital Flipbook Pada Mata Pelajaran Geografi Materi Keanekaragaman Hayati - Pakaya, Haerunnisa; Maryati, Sri; Pambudi, Moch Rio (Universitas Negeri Gorontalo, 2025)
Education is a vital aspect in addressing the challenges of the 21st century. With the rapid development of globalization, the industrial revolution 4.0, and social changes, education becomes the key to preparing individuals to succeed and remain relevant in the modern era. One crucial aspect of 21st-century education is the ability to adapt to rapid changes. The integration of technology in learning, especially through the use of digital Flipbooks, provides an innovative approach to delivering educational content. Digital Flipbooks serve as interactive teaching media that enhance students' understanding and motivation. This study focuses on designing and developing a digital Flipbook for teaching biodiversity in geography, aligned with the Merdeka Curriculum. The Flipbook incorporates multimedia elements such as text, images, videos, animations, and interactive quizzes to create a meaningful and effective learning experience. The findings suggest that the Flipbook significantly enhances students' comprehension and engagement in learning biodiversity topics.